Comparative analysis of menus in the Northern and Southern Great Plain touristic regions - Sándor, Dénes (Applied Studies in Agribusiness and Commerce, 2011)
The background of the study is based on previous studies dealing with the areas of Transdanubia and Central Hungary. Those works have proved the hypothesis of author that local ingredients and dishes represent minimum role on menus. The question is how similar or different the choice of menus of Northern and Southern Great Plain is from the previously examined areas of Hungary.Additional questions may also arise in terms of the usage of local ingredients available near catering units. This piece of work has studied several menus of Northern and Southern Great Plain, Hungary. The material was collected from different types of restaurants, ‘csárda’-s and inns. The methodology was two-tier: data collecting on the one hand, and the detailed examination of differences between the catering units on the other hand: the number of dishes, the right order of dishes, the appearance of local ingredients and dishes, the consideration of seasonality, the usage of different cooking methods and group of dishes. The study reflects the main problems of countryside restaurants in Hungary. Only a minimum number of dishes could be connected to local dishes out of more thousands.All in all, dishes are not as precise and perfect as the ‘old ones’used to be; that is why it is important for every expert to keep traditions alive in daily routines and by way of strategic means too.